2022
DOI: 10.34172/jrhs.2022.99
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Helmet Use Behavior among Motorcyclists Based on the Theory of Planned Behavior

Abstract: Background: Road traffic injuries (RTIs) are one of the most critical factors that endanger human health. More specifically, head and neck injuries are the main causes of deaths and disabilities among motorcyclists. This study aimed to investigate the predictive factors of helmet use behavior among motorcyclists based on the theory of planned behavior (TPB). Study Design: This study followed the cross-sectional design. Methods: This study was conducted on randomly selected 730 motorcyclist employees in Qom, Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A researcher-developed questionnaire, based on previous studies (11,27), was used to collect data, and its validity and reliability were subsequently examined. For further, easier, and faster access by the participants to the questionnaire, the link and QR code of the questionnaire were shared through the organizational automation network and the government network.…”
Section: Data Collection Instruments and Strategymentioning
confidence: 99%
“…A researcher-developed questionnaire, based on previous studies (11,27), was used to collect data, and its validity and reliability were subsequently examined. For further, easier, and faster access by the participants to the questionnaire, the link and QR code of the questionnaire were shared through the organizational automation network and the government network.…”
Section: Data Collection Instruments and Strategymentioning
confidence: 99%
“…In addition, it considers approximately 3% of the gross domestic product in 2018. 1 , 2 Although all RTCs are problematic, research shows that fatality rates in suburban regions are greater. 3 , 4 Suburban roadways play a transitional high-speed roadway role in connecting low-speed urban roads with high-speed rural highways.…”
Section: Introductionmentioning
confidence: 99%
“…Helmets are not mere accessories but serve as essential safety equipment to mitigate the severity of head injuries in the event of an accident [12]. Several studies, have consistently shown a direct correlation between not wearing helmets and head injuries resulting from traffic accidents [13], [14]. As a response to these risks, the Indonesian government has enacted laws mandating the use of helmets that meet national safety standards [15].…”
Section: Introductionmentioning
confidence: 99%